Esri Italia presenta tutte le nuove funzionalità di ArcGIS 10.2 - Italia, Esri (GEOmedia, 2013)
After the succ ess of the previous version, the new release of Arc GIS 10.2 makes further progress towards the transformation of the GIS system to manage geographic information at complete platform for fundamentally transform workflows. The innovations involve both the Desktop and Serv er, both kits for developers both the tools of Arc GIS Online.